E-Government Implementation Evaluation in Local Government Agency in Pontianak Regency - Bagus Pramono (Institut Pemerintahan Dalam Negeri (IPDN), 2019)
ASN in Pontianak since 2016 until now, the provision of public services very rarely inthe District various utilizes have been used e-government applications. However,people who want to apply for services must still use conventional methods. The purposeof this study to analyze and find out the things that led not to achieving the objectivesof the implementation of e-government in the district agencies in Pontianak. It find outand analyze the factors that influence about the innovation e-Government applicationin the District agencies in Pontianak. The type of research used descriptive qualitativeresearch. Determination of informant to get source of data on the results of this studywas determined through purposive sampling technique. Data collection techniquesused by interviews, document review and observation. The results of this study indicatethat the implementation of e-government in sub-district agencies in Pontianak is less.The factors that influence about the implementation of e-government innovation in theDistrict agencies in Pontianak, there is no clarity of the specific objectives to beachieved. In this case the purpose of implementing e-government is unclear. There areunclear and measurable targets, so that it causes bias in the implementation of egovernment.The ambiguity of the priority target groups. Unclear policy instrumentsas terms of reference in the form of technical procedures (operational / technicalguidelines) both administratively and technically with clear boundaries for articulatingthe policy program for implementing e-government.